Handbook of research on social and organizational liabilities in information security - Gupta, Manish, 1978-; Sharman, Raj. (Hershey, PA : Information Science Reference, 2009)
'This book offers insightful articles on the most salient contemporary issues of managing social and human aspects of information security'--Provided by publisher.
Includes bibliographical references (p. 503-540) and index.
Keywords: Computer security -- Management -- Handbooks, manuals, etc; Data protection -- Management -- Handbooks, manuals, etc; Computer crimes -- Prevention -- Handbooks, manuals, etc; Human-computer interaction -- Handbooks, manuals, etc